2020
DOI: 10.21203/rs.3.rs-60179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily Mean Temperature and HFMD: Risk Assessment and Attributable Fraction Identification in Ningbo China

Abstract: Background: Hand, foot and mouth disease (HFMD) remains a significant public health issue, especially in developing countries. Many studies have reported the association between environmental temperature and HFMD. However, the results are highly heterogeneous in different regions. In addition, there are few studies on the attributable risk of HFMD.Objectives: The study aimed to assess the association between temperature and HFMD incidence and to evaluate the attributable burden of HFMD in Ningbo China.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…There was evidence that women were more vulnerable to cold temperatures than men [39]. The age-specific results showed that children aged 0-1 were more vulnerable to warm temperature and the CRR was the highest, which was consistent with other studies [9,15]. It has been reported that maternal antibody levels to EV71 declined one month after birth, and thus the lack of immunity increased the susceptibility of children under 1 year of age to temperature [40].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There was evidence that women were more vulnerable to cold temperatures than men [39]. The age-specific results showed that children aged 0-1 were more vulnerable to warm temperature and the CRR was the highest, which was consistent with other studies [9,15]. It has been reported that maternal antibody levels to EV71 declined one month after birth, and thus the lack of immunity increased the susceptibility of children under 1 year of age to temperature [40].…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to the fact that children aged 3-6 were more likely to gather in a closed environment in cold weather (such as kindergartens), and worse indoor ventilation in cold days might facilitate the transmission of HFMD [41]. However, cold temperature was a protective factor associated with HFMD for scattered children, possibly because they were more likely to stay at home and reduce outdoor activities in cold weather, thus they had less opportunities to contact with each other and be exposed to contaminants [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation